Penetapan Kadar Formalin pada Tahu Putih yang Dijual di Pasar Kranggan Bekasi dengan Metode Spektrofotometri UV-Vis pada April 2025 - Ivan Santoso; Pricillya Maria Loimalitna; Wulan Sucianingrum; Pra Panca Bayu Chandra; Indri Astuti Handayani (Jurnal Ilmu Farmasi Terapan dan Kesehatan, 2025)
The misuse of formalin as a preservative in food products, particularly white tofu, is still frequently found, despite its prohibition due to harmful health effects such as respiratory tract irritation, internal organ damage, and even cancer risk. White tofu is one of the food items that is vulnerable to formalin addition to extend its shelf life and improve texture. The aim of this study was to identify and determine the formalin content in white tofu sold at Kranggan Market, Bekasi, using the UV-Vis spectrophotometry method. This research employed a descriptive quantitative method. The analysis was carried out through both qualitative and quantitative testing on 14 white tofu samples obtained from Kranggan Market. The qualitative test, using Schiff reagent, KMnO₄, and Fehling’s solution, showed that 7 samples gave positive reactions indicating the presence of formalin. The quantitative test was conducted using UV-Vis spectrophotometry at a maximum wavelength of 550 nm, and a standard curve was obtained with a correlation coefficient (R) of 0.991. The results showed that 8 samples contained formalin, with concentrations ranging from 0.00018% w/w to 0.00104% w/w. The UV-Vis spectrophotometry method proved to be sensitive and accurate in detecting formalin in food samples. These findings indicate that some white tofu sold at Kranggan Market still contains formalin, highlighting the need for stricter food safety monitoring in traditional markets.